2016
DOI: 10.1039/c6dt02378a
|View full text |Cite
|
Sign up to set email alerts
|

Triple molybdate scheelite-type upconversion phosphor NaCaLa(MoO4)3:Er3+/Yb3+: structural and spectroscopic properties

Abstract: Triple molybdate NaCaLa(MoO):xEr,yYb (x = y = 0, x = 0.05 and y = 0.45, x = 0.1 and y = 0.2, x = 0.2 and y = 0) phosphors were successfully synthesized for the first time by the microwave sol-gel method. Well-crystallized particles formed after heat treatment at 900 °C for 16 h showed a fine and homogeneous morphology with particle sizes of 2-3 μm. The structures were refined by the Rietveld method in the space group I4/a. The optical properties were examined comparatively using photoluminescence emission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…29,36 For example, Lim and co-workers observed excellent luminescence properties in NaCaLa(MoO 4 )O 3 :Er 3+ ,Yb 3+ phosphors. 37 A similar phenomenon was also observed in NaSrLa(MoO 4 ) O 3 :Er 3+ ,Yb 3+ compounds. 38 Considering the above discussion and the fact that the NaSrLa(MoO 4 )O 3 structure has not been thoroughly investigated, the Er 3+ -activated NaSrLa(MoO 4 )O 3 was selected as a representative sample to verify the dual-functional applications of the rare-earth ion-activated molybdates in pc-LED devices and non-contact optical thermometry.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…29,36 For example, Lim and co-workers observed excellent luminescence properties in NaCaLa(MoO 4 )O 3 :Er 3+ ,Yb 3+ phosphors. 37 A similar phenomenon was also observed in NaSrLa(MoO 4 ) O 3 :Er 3+ ,Yb 3+ compounds. 38 Considering the above discussion and the fact that the NaSrLa(MoO 4 )O 3 structure has not been thoroughly investigated, the Er 3+ -activated NaSrLa(MoO 4 )O 3 was selected as a representative sample to verify the dual-functional applications of the rare-earth ion-activated molybdates in pc-LED devices and non-contact optical thermometry.…”
supporting
confidence: 63%
“…Recently, molybdates have been extensively investigated due to their excellent luminescent properties, high stability and relatively low synthesis temperature . For example, Lim and co‐workers observed excellent luminescence properties in NaCaLa(MoO 4 )O 3 :Er 3+ ,Yb 3+ phosphors . A similar phenomenon was also observed in NaSrLa(MoO 4 )O 3 :Er 3+ ,Yb 3+ compounds …”
Section: Introductionmentioning
confidence: 72%
“…In the previous Raman evaluation of complex molydates, it was demonstrated that Raman mode with highest wavenumber was ascribe to shortest Mo–O bond vibration according to relation between bond length and predicted of ν (cm −1 ) . Furthermore, in double molybdates, the modes wavenumbers observed over 130‐190 cm −1 are classified as translations of Gd ions …”
Section: Resultsmentioning
confidence: 98%
“…58 Furthermore, in double molybdates, the modes wavenumbers observed over 130-190 cm −1 are classified as translations of Gd ions. [59][60][61][62]…”
Section: Raman Spectroscopy and Vibrational Mode Analysismentioning
confidence: 99%
“…The UC spectrum of YF 3 :Yb 3+ , Er 3+ contains five distinctly detectable emission bands of Er . Especial interest is the presence of 4 H 9/2 – 4 I 15/2 transition that requires participation of at least three pump photons for the excitation of 4 H 9/2 energy level.…”
Section: Resultsmentioning
confidence: 99%